Abundance matters: role of albumin in diabetes, a proteomics perspective - Bhat, Shweta; Jagadeeshaprasad, Mashanipalya G.; Venkatasubramani, Vinashya; Kulkarni, Mahesh J. (Expert Review of Proteomics, 2017)
Introduction: Human serum albumin (HSA) is a multifaceted protein with vital physiological functions. It is the most abundant plasma protein with inherent capability to bind to diverse ligands, and thus susceptible to various post-translational modifications (PTMs) which alter its structure and functions. One such PTM is glycation, a non-enzymatic reaction between reducing sugar and protein leading to formation of heterogeneous advanced glycation end products (AGEs). Glycated albumin (GA) concentration increases significantly in diabetes and is implicated in development of secondary complications. Areas covered: In this review, we discuss in depth formation of GA and its consequences, approaches used for characterization and quantification of GA, milestones in GA proteomics, clinical relevance of GA as a biomarker, significance of maintaining abundant levels of albumin and future perspectives. Expert commentary: Elevated GA levels are associated with development of insulin resistance as well as secondary complications, in healthy and diabetic individuals respectively. Mass spectrometry (MS) based approaches aid in precise characterization and quantification of GA including early and advanced glycated peptides, which can be useful in prediction of the disease status. Thus GA has evolved to be one of the best candidates in the pursuit of diagnostic markers for prediction of prediabetes and diabetic complications.